Knowledge of Farmers About Farm Pond Covered Under Krishi Bhagya Yojane in Karnataka - Satapathy, Guru Prasad; Dolli, S. S.; Gowda, Rajendra D.; Jayasingh, Debi Kalyan (Indian Journal of Extension Education, 2022)
The study was undertaken in Shivamogga and Uttara Kannada districts of Karnataka on 80 farmers during 2020-21 to assess the farmers’ knowledge about farm ponds as part of the Krishi Bhagya Yojane (KBY). The primary data on farmers’ knowledge about farm ponds under Krishi Bhagya Yojane was acquired by employing schedule developed for it. All the farmers had knowledge of KBY as a ‘scheme for storing runoff water’, ‘funded by Government of Karnataka’ and ‘Raitha Samparka Kendra as contact office’. Large majority the farmers (98.75%) had knowledge about ‘farm pond, polythene sheet, diesel engine and sprinkler set components’ and 86.25 per cent of farmers had knowledge about ‘polythene sheet to prevent percolation’. 97.50% of farmers had knowledge about ‘subsidy given for all the farmers’ and majority of farmers (87.50%) had knowledge about subsidy given for ‘dugout of farm pond. Knowledge was positively significant with education, economic motivation and area under commercial agriculture, extension contact, mass media exposure, cropping intensity and area under irrigation. 48.70 per cent of variation in knowledge was explained by all the independent variables selected for the study.
Keywords: Krishi Bhagya Yojane; Farm Pond; Knowledge; Farmers; Rainfall